Symbole wielokulturowości w przestrzeni publicznej na rzecz przeciwdziałania nietolerancji - Walancik , Marek (Studia Edukacyjne, 2020)
Walancik Marek, Symbole wielokulturowości w przestrzeni publicznej na rzecz przeciwdziałania nietolerancji [Symbols of Multiculturalism in Public Space to Counteract of Intolerance]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 111-127. Adam Mickiewicz University Press. ISSN 1233-6688. DOI:10.14746/se.2020.56.6 In the article, the author addresses the issue of the essence and role of the symbol of multiculturalism in public space in the context of counteracting intolerance. The presented text contains not only a presentation of basic terms and theories, but also an analysis of empirical research results related to the issue of the significance of the symbol of multiculturalism in order to counteract intolerance. Frequently appearing facts of intolerance towards culturally different individuals lead to reflection and seeking answers to the question: Does the presence of a symbol of multiculturalism in public space, which was once a borderland space, and today is saturated with various forms of symbols of multiculturalism of the past and of the modern period affect behavior tolerance.